Pork Marketing Channels through Slaughterhouses and Traditional Markets - Oroh, Franky N.S (Jambura Journal of Animal Science, 2024)
Pigs are prolific and efficient in animal husbandry industry. The purpose of this study was to find out marketing channels, sales on the Bersehati market, and margin by each marketing agency involved in these marketing channels. The type of data used in this study was quantitative data from primary data and secondary data. The results showed that for the characteristics of the average age of repondents ranged from 41-60 years. The educational characteristics of respondents show that the average education in high school. Characteristics of Respondents' Length of Business show that the average was 11-20 years. Traders who have experienced their business will be more skilled and tend to produce better results than inexperienced traders. The job characteristics of respondents show quite varied, producers have jobs as ranchers, collecting traders and retailers as entrepreneurs, end consumers as housewife, civil servants and entrepreneur. There were 2 marketing channels, namely: Channel 1 consists of producers, retailers and final consumers. Channel 2 consists of producers, collectors, retailers and final consumers. There are 3 institutions involved in the pork marketing channel process, namely producers, collecting traders, and retailers. Marketing margin for channel 1 was manufacturer 0, retailer IDR. 640.000. Margin for channel 2 was producer 0, merchant collector IDR.300.000, merchant retailer IDR. 440.000 with total margin IDR. 740.000.